The study on the use of project success framework among project personnel / Joshua Suring - Joshua , Suring (2020)
Projects, programs and portfolios are essential for human endeavors since time immemorial. However, project success rates in various sectors are dismal and not up to expectations. This research aims to investigate the use of a multilevel project success framework among project personnel in various sectors to identify essential success levels and criteria and determine any weaknesses and gaps for enhancing the framework. This is a qualitative study during which a conceptual framework was developed and tested with data gathered using a questionnaire survey with open-ended questions which was distributed to project personnel based on snowball sampling. A total of 52 responses out of 500 questionnaires sent out were received, giving a response rate of 10.4%. The results found six levels and criteria of the project success continuum in addition to existence of the stakeholder and derived value continuums, several gaps in the use and weaknesses of the project success frameworks and thus the framework was enhanced by adding the input level, owner and sponsor and customer into the stakeholder continuum and operational value to the value continuum. Past researches show no agreement and consensus on a standardized and holistic project success framework, lack of empirical evidence of its relevance, completeness of its criteria and its practical utility and bifurcation between project management and project successes from the outcome and impact success levels. This research provides an enhanced multilevel project success framework with three continuums, the required empirical evidence for the framework and the integration of the bifurcated success continuum which can be used by project personnel to accomplish project success and organization performance excellence in general.